COORDINATION OF COLOR AND RAGA: IN THE CONTEXT OF KANGRA PAINTINGS: रंग और राग का समन्वयः काँगड़ा चित्रों के संदर्भ में - Gautam, Manju (International Journal of Research -GRANTHAALAYAH, 2014)
The amazing coordination of music and painting in Kangra painting is a unique achievement in arts across the world, which is why Kangra painting is considered by art scholars to be synonymous with all hill painting. The color scheme of the paintings produced in the Kangra painting style is unique, it seems that all the beauty of the Kangra aesthetic artist filled the paintings through color and lines. The diversity of subjects is a quality of this genre. The artist here also gave the form of abstract and phonetic content of music along with literature and poetry, by color and lines, which is rare in any other art of the world. काँगड़ा चित्रकला में संगीत व चित्रकला का अद्भूत समन्वय संसार भर की कलाआंे मंे एक अद्वितीय उपलब्धि है यही कारण है कि काँगड़ा चित्रकला को कला विद्वानों ने समस्त पहाड़ी चित्रकला का पर्याय भी माना है। काँगड़ा चित्रशैली में निर्मित चित्रो की रंग योजना अनूठी है ऐसा प्रतीत होता है कि काँगड़ा का समस्त प्रकृति सौन्दर्य कलाकार ने रंग व रेखाओं के माध्यम से चित्रों में भर दिया। विषयों की विविधता इस शैली का गुण है। यहाँ के कलाकार ने साहित्य एवं काव्य के साथ संगीत की अमूर्त, तथा ध्वन्यात्मक विषय वस्तु को भी रंग एवं रेखाओं द्वारा साकार रूप प्रदान किया जो कि विश्व की किसी अन्य कला में दुर्लभ है।